Pengaruh Pemberian Mol Rebusan Kedelai dan Air Cucian Beras terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum L.) - Syaiful Rijal, Moch. Ayyub; ARINI, SILVIA (Program Studi Agroteknologi, 2024)
This research aims to determine the effect of mole treatment of boiled soybeans and rice washing water on the growth and yield of tomato gardens. This research was carried out in Sukorambi Village, Sukorambi District, Jember, East Java. starting October 2022 to January 2023. The research was conducted using a Randomized Block Design (RAK) consisting of 2 factors and 3 replications. The first factor is the Mole Boiled Soybean (M) treatment which consists of 4 levels, namely (control) M1 = 20 m1/1, M2 = 20 m1/1, M3 = 60 m1/1, M4 = 80 m1/1, and the second factor is Rice Washing Water (B) which consists of 4 levels, namely (control) B0 = 0 ml/1, B1 = 100 ml/1, B2 = 200 ml/1, B3 = 300 ml/1. The parameters observed were plant height, stem diameter, number of fruit per plant, number of branches, initial appearance of flowers, fruit diameter, fruit weight. The collected data was analyzed using variance (Anova), if significantly different, continued with the Duncan test at the 5% level using Microsoft Excel. The results of the research showed that the treatment of mole boiled soybeans and rice washing water for each observation parameter showed results that were not significantly different.